열처리와 Shoot-Tip Grafting에 의한 감귤 바이러스 무독묘 생산 - 김대현(Dae Hyun Kim); 심혜경(Hye Kyung Shim); 권혁모(Hyeog Mo Kwon); 현재욱(Jae Wook Hyun); 김광식(Kwang Sik Kim); 이진경(J (Journal of plant biotechnology, 2005)
Virus-free stocks was produced by the combination of the heat treatment of virus infected plant and shoot-tip grafting (STS). To produce virus-free stocks, the plants infected with citrus viruses were used for virus-free stock production using the modified method of STG in thermotherapy at $40^{°}C$ for 16 hours in the light, and at $30^{°}C$ for 8 hours of darkness for 4 weeks. Trifoliate orange (P. trifoliata) were used as rootstock seedling for STG. Percentages of virus-free stocks against citrus tristeza virus (CTV), satsuma dwarf virus (SDV) and citrus tatter leaf virus (CTLV) were $75.7%,\;100.0,%\;82.6%$ respectively. Shoot tip size for successful STG were as small as possible. Less than $0.3\;\cal{mm}$ of shoot tips gave the hight efficiency of virus free plants but survival rates were low. And, survival rate after shoot-tip culture was analyzed and the rates were dependant on the cultivars; Yuzu cultivar showed the hight survival rate ($74.6%$) and early satsuma mandarin (Iwasagi) was $13.3%$ as the lowest cultivar. But citrus trees were not succeed to grown, turned brown, and died. 바이러스에 감염된 감귤나무를 생육상에서 주간 $40^{°}C$, 야간 $30^{°}C$로 열처리한 후 발생한 신초를 $0.3\~0.7\;\cal{mm}$ 로 잘라내어 기내에서 치상한 탱자 (P. trifoliata) 대목에 접목하는 열처리와 경정접목 (shoot-tip grafting)을 병행한 방법으로 무독묘 생산에 성공하였다. 감글 바이러스 즉, citrus tristeza virus (CTV), satsuma dwarf virus (SDV) and citrus tatter leaf virus (CTLV) 에 대한 무독화율은 각각 $75.7%,\;100.0,%\;82.6%$ 였다. 경정접목 시 접수크기는 $0.3\;\cal{mm}$ 이하 일때 바이러스 무독화율이 높았으나 절목 후 활착율은 저하되었다. 열처리 후 경정배양 (shoot-tip culture)을 하여 1 개월 후에 활착율을 조사한 결과 Yuzu (C. junos)는 $74.6%$, 그리고 early satsuma mandarin (Iwasagi)은 $13.3%$를 나타내었다. 그러나 항바이러스제인 rivabirin을 첨가한 후 무독효과를 보기 위하여 후대배양 중에 온주밀감의 특성상 갈변되어 고사함으로서 무독묘를 생산하지 못했다.